Pengaruh Fear of Missing Out terhadap Psychological Well-Being pada Mahasiswa di Kota Bandung - Azka Salsabila Novaro; Milda Yanuvianti (Bandung Conference Series: Psychology Science, 2024)
Abstract. Psychological well-being is important for every individual to have because it affects various things in human life. With the development of technology, especially social media, it also affects the way individuals interact, share information, and form perceptions about themselves and the environment around them. The development of social media also provides new challenges, one of which is the FoMO phenomenon. Exposure to various contents of other people's lives on social media can trigger social comparison and feelings of dissatisfaction in individuals. One social media that has the potential to trigger FoMO behavior is Instagram. This study aims to find out how much influence FoMO has on Psychological Well-Being in university students in Bandung City. Using quantitative methods with 319 respondents, obtained by convenience sampling technique. Respondent criteria are active students at several universities in Bandung City and active Instagram users. The measuring instruments used are the Fear of Missing Out Scale compiled by Przybylski (2013) and adapted by Santika (2015), and the Psychological Well-Being Scale compiled by Ryff (1989) and adapted by Rachmayani and Ramdani (2014). The results show that FoMO has a negative influence of 13.5% on Psychological Well-Being in university students in Bandung City. The higher the level of FoMO, the lower the level of Psychological Well-Being. While the other 86.5% can be influenced by other variables, one of which is the variable of social media addiction (Parveiz et al, 2023). Abstrak. Psychological Well-Being penting untuk dimiliki setiap individu karena berpengaruh dalam berbagai hal di kehidupan manusia. Dengan perkembangan teknologi khususnya sosial media berpengaruh pula pada cara individu berinteraksi, berbagi informasi, dan membentuk persepsi tentang mereka juga lingkungan disekitarnya. Perkembangan media sosial juga memberikan tantangan baru, yaitu salah satunya fenomena FoMO. Paparan dari berbagai konten kehidupan orang lain di media sosial dapat memicu perbandingan sosial dan perasaan tidak puas pada individu. Media sosial yang berpotensi memicu perilaku FoMO salah satunya adalah Instagram. Penelitian ini bertujuan untuk mengetahui seberapa besar pengaruh FoMO terhadap Psychological Well-Being pada mahasiswa di Kota Bandung. Menggunakan metode kuantitatif dengan 319 responden, yang diperoleh dengan teknik convenience sampling. Kriteria responden merupakan mahasiswa aktif di beberapa perguruan tinggi di Kota Bandung dan pengguna aktif Instagram. Alat ukur yang digunakan adalah Fear of Missing Out Scale yang disusun oleh Przybylski (2013) dan diadaptasi oleh Santika (2015), serta Psychological Well-Being Scale yang disusun oleh Ryff (1989) dan diadaptasi oleh Rachmayani dan Ramdani (2014). Hasilnya menunjukan bahwa FoMO memiliki pengaruh negatif sebesar 13,5% terhadap Psychological Well-Being pada mahasiswa di Kota Bandung. Semakin tinggi tingkat FoMO maka semakin rendah tingkat Psychological Well-Being. Sementara 86,5% lainnya dapat dipengaruhi oleh variabel lain, salah satunya pada variabel adiksi media sosial (Parveiz et al, 2023).